Toward an Islamic theology of nonviolence: in dialogue with René Girard - Maqrānī, ʿAdnān al- (Studies in violence, mimesis, and culture, 2022)
"This book offers a study of the Qur'ān and Islamic history in the light of René Girard's mimetic theory, going beyond just war theory to adopt a nonviolent approach"--